The discursive construction of Rousseff's hysterization (Simbiótica. Revista Eletrônica, 2025)
This article analyzes the exclusion of women from contemporary Brazilian political space, taking as an exemplary case the trajectory of former president Dilma Rousseff, the target of a process of symbolic delegitimization based on her association with hysteria, a mechanism historically used to control and banish the feminine that breaks with normative gender standards. The research focuses on the discursive analysis of journalistic articles that portray Dilma as unbalanced and undesirable, culminating in her banishment from the Grupo Prerrogativas dinner in 2021. The text relates these episodes to the concept of the cloister of hysteria, showing how misogyny structures the exclusion of women from power through discourses that combine dehumanization, social control, and symbolic violence. Based on the above, the articles “A president out of her mind” (IstoÉ), “Dilma, the swindler, deserved to become the successor of Maria I, the Mad” (Veja) and “Dilma became moribund like a zombie and no one wants her back in power” (Folha de São Paulo) will be analyzed, relating to the non-invitation to the dinner.
Keywords: Political Territory; Women; Cloister of Hysteria; Dilma Rousseff